Assessment of Awareness, Knowledge, Attitude, and the Practice of Vitamin D among the General Public in Malaysia - Blebil, Ali Qais; Dujaili, Juman Abdulelah; Teoh, Enie; Wong, Pik Sze; KC, Bhuvan (Journal of Karnali Academy of Health Sciences, 2019)
Background: Vitamin D deficiency is becoming a global epidemic, which is still undertreated despite increased treatment availability and increase in therapeutic options. This study aimed to explore the awareness, knowledge, attitude and practices regarding Vitamin D among the general public in Malaysia.Methods: A cross-sectional survey was carried out in a public area using a convenience samplingtechnique to recruit participants around Selangor and Kuala Lumpur shopping malls area. An anonymous self-administeredquestionnaire was used for data collection and it was circulated to 603 Malaysian. A total of 400 participants were completed and returned to the researchers.  Result: Although 90.5% of the participants have heard/learnt about Vitamin D. About 78.0% of them showed limited knowledge about some aspects of Vitamin D with (mean ± SD = 1.78 ± 0.894). Additionally, there was a negative attitude towards Vitamin D and sunlight exposure. For instance, nearly 70.0% of the respondents did not like to expose themselves to sunlight.  Only 30.0% of the participants had taken Vitamin D supplement before.There is a small, positive correlation between the knowledge score and education level, rho = 0.124, n = 400, P = 0.013, with a higher score associated with higher education level.Conclusion: The findings provided a piece of contemporary real-world evidenceon the lack of knowledge and practices about Vitamin D among the general public. Therefore, extensive health educational campaigns for the public should be implemented by the government to raise their knowledge on the importance of Vitamin D.